Adjustment and social support at work early after breast cancer surgery and its associations with sickness absence. Issue 12 (3rd July 2013) - Nilsson, Marie I.; Petersson, Lena‐Marie; Wennman‐Larsen, Agneta; Olsson, Mariann; Vaez, Marjan; Alexanderson, Kristina
Abstract Introduction As half of the women with breast cancer are of working ages and usually survive, knowledge is needed on how to support them early regarding work‐related problems caused by treatments. Most previous studies have focused on individual and disease‐related factors, whereas few have focused on work‐related factors such as work adjustment and social support. The aim of this study was to investigate received and perceived social support from supervisor and colleagues as well as work adjustments, and their associations with sickness absence, among women who recently had had breast cancer surgery. Method Inclusion criteria were as follows: women aged 20–63 years, living in Stockholm County, treated surgically for a first diagnosis of breast cancer, literate in Swedish, without pre‐surgical chemotherapy or known distant metastases. Included in the study were 605 women who worked at diagnosis and that had answered a questionnaire within eight weeks of inclusion. Descriptive statistics, univariate, and multivariable logistic regression analyses were applied to estimate odds ratios (OR) with 95% confidence intervals (CI) for the likelihood of being sickness absent. Results Most women perceived and received social support and work adjustment after breast cancer surgery. Low adjustment (OR = 2.14; 95% CI, 1.45–3.18) and less social support (OR = 1.80; 95% CI, 1.16–2.78) were significantly associated with being sickness absent. Adjusting for sociodemographics, strenuous work posture, and treatment did not attenuate these associations. Conclusion Adjustment at work and social support from employer are associated with sickness absence and needs to be explored in discussions on return to work after breast cancer surgery. Copyright © 2013 John Wiley & Sons, Ltd.